2021
DOI: 10.3390/molecules26185578
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-Cereal Blend Extrusion for Improving the Antioxidant Properties of a Gluten-Free Flour

Abstract: Extrusion is an interesting technological tool that facilitates pulse formulation into flour mixtures, with tailored fibre content, total antioxidant capacity (TAC) and glycemic index (GI) among other components in final formulas. The gluten-free (GF) market has significantly grown during the last years. GF products have evolved from specialty health foods to products targeted to the general population and not only associated to celiac consumers. This study evaluates how temperature, cereal base (rice/corn) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 91 publications
3
6
0
Order By: Relevance
“…Rice flours (M1 and E1) had the lowest TP values (24.3 and 18.2 mg GAE 100 g −1 respectively). These results agreed with the previous studies reported [ 56 , 88 ], where it was observed that rice flours after extrusion significantly reduced ( p ≤ 0.05) its phenolic content, which may demonstrate that the phenolic compounds in rice flours are more thermally sensitive than in other flours.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Rice flours (M1 and E1) had the lowest TP values (24.3 and 18.2 mg GAE 100 g −1 respectively). These results agreed with the previous studies reported [ 56 , 88 ], where it was observed that rice flours after extrusion significantly reduced ( p ≤ 0.05) its phenolic content, which may demonstrate that the phenolic compounds in rice flours are more thermally sensitive than in other flours.…”
Section: Resultssupporting
confidence: 93%
“…Carbohydrate content was similar in RF to values reported by other authors [ 56 ], and in teff flours, values were slightly higher (81.67 to 81.97 g 100 g −1 ) than those reported by other authors, where teff carbohydrates reached values of 73.1 and 73.6 g 100 g −1 [ 68 ]. A significant reduction of carbohydrates was found, similarly to other authors who have previously reported decreases in carbohydrates after extrusion of cereal matrices [ 69 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The comparison of the sorption isotherms of raw materials from sour cherry and blackcurrant pomaces and extrudates from the same pomaces with the addition of corn meal showed a reduction of the sorption capacity of the extrudates (Witczak et al, 2020). Rico et al (2021) indicated that the extrusion increased the hydrophobic interaction of proteins with other compounds such as starch and lipids. For example, the proteins and/or amino acids chemically react with reducing sugars at a high temperature which leads to the formation of hydrophobic melanoidins.…”
Section: Resultsmentioning
confidence: 99%